Laleonectes vocans ... - In, First Published (Zenodo, 2022)
Laleonectes vocans (A. Milne-Edwards, 1878) (Fig. 28A–D) Neptunus vocans A. Milne-Edwards, 1878: 225. Trindade specimens. 1 male (MZUSP 40172), Brazil, off Espírito Santo, Trindade Island, Enseada dos Portugueses, SECON, 20°30’20.9”S, 29°18’43.7”W, J.B. Mendonça coll., 29.iv.2014, 0.9 m. 1 male (MZUSP 40174), ibidem, Enseada dos Portugueses, 20°30’17.7”S, 29°18’56.7”W, J.B. Mendonça coll., 18.iv.2014, 10.2 m. 1 male (MZUSP 40179), ibidem, Ponta da Calheta, 20°30’16.59”S, 29°18’30.11”W, J.B. Mendonça coll., 30.i.2019, 15.1 m. 1 male (MZUSP 39659), ibidem, 20°30’18.72”S, 29°18’31.6”W, J.B. Mendonça coll., 25.vii.2018, 15.6 m. 1 juvenile (MZUSP 41418), ibidem, J.B. Mendonça coll., 20.vii.2014, 16.3 m. 1 juvenile (MZUSP 41469), R/V “Marion Dufresne”, TAAF MD55/Brésil Expedition, Ponta da Calheta, stn 35 DC59, 20°30.37’S, 29°18.55’W, 22.v.1987, 60 m. 1 male (MZUSP 33836), ibidem, Ilha da Racha, 20°30’26.5”S, 29°20’48”W, J.B. Mendonça coll., 3.vi.2015, 23 m. 1 juvenile (MZUSP 39620), ibidem, 30.vii.2018, 24.8 m. 1 ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on pages 54-55, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...